Cellulose-Based Nanofibril Composite Materials as a New Approach to Fight Bacterial Infections - Rashki, Somaye; Shakour, Neda; Yousefi, Zahra; Rezaei, Marzieh; Homayoonfal, Mina; Khabazian, Ehsan; Atyabi, Fatemeh; Aslanbeigi, Fatemeh; Safaei Lapavandani, Rouzita; Mazaheri, Samaneh; Hamblin, Michael R; Mirzaei, Hamed (Frontiers in Bioengineering and Biotechnology, 2021)
Antibiotic resistant microorganisms have become an enormous global challenge, and are predicted to cause hundreds of millions of deaths. Therefore, the search for novel/alternative antimicrobial agents is a grand global challenge. Cellulose is an abundant biopolymer with the advantages of low cost, biodegradability, and biocompatibility. With the recent growth of nanotechnology and nanomedicine, numerous researchers have investigated nanofibril cellulose to try to develop an anti-bacterial biomaterial. However, nanofibril cellulose has no inherent antibacterial activity, and therefore cannot be used on its own. To empower cellulose with anti-bacterial properties, new efficient nanomaterials have been designed based on the development of cellulose-based nanofibrils as potential wound dressings, food packaging, and other antibacterial applications. In this review we summarize reports concerning the therapeutic potential of cellulose-based nanofibrils against various bacterial infections